Pengaruh Gaya Kepemimpinan dan Loyalitas Terhadap Kinerja Karyawan di Bagian Keperawatan RSUD Sultan Imanuddin Pangkalan Bun - Ayu Dwi Puspita (Universitas Ahmad Dahlan, 2021)
Hospitals have the largest resources occupied by nurses. Nurses have a position that is sufficient to determine the level of quality of health services in the hospital so that the performance of nurses needs to be improved. To optimize this, the hospital needs to pay attention to the factors that affect the performance of nurses, including leadership style and employee loyalty. Leadership style is the way a leader influences, directs, motivates, and controls employees in a certain way so that employees can complete tasks effectively and efficiently. Loyalty is employee loyalty to an organization or devotion to a company organization which is manifested by the willingness of employees to carry out company duties with full awareness and responsibility so that the company's goals can be achieved. The purpose of this study was to determine the effect of leadership style and loyalty on employee performance in the nursing department of the Sultan Imanuddin Pangkalan Bun hospital. This type of research is quantitative with a cross-sectional approach. The sampling technique used the accidental sampling technique. The study population was all 180 nurses at Sultan Imanuddin Pangkalan Bun Hospital. The sample size was 51 nurses obtained using the Iemesshow formula. The results of the chi square test show that there is no influence between leadership style on employee performance with a p-value of 0.091 (p> 0.05) and there is an influence between loyalty to employee performance with a value of p-value 0.000 (p <0.05). There is no influence between the variable leadership style and employee performance, There is an influence between the variable loyalty to employee performance.